Lewis superacids: classifications, candidates, and applications - Greb, Lutz (Chemistry - a European journal, 2018)
Abstract Lewis acids play a major role in all areas of chemistry. For a long time, toxic, corrosive and oxidizing SbF5 was considered as the strongest Lewis acid known. Lately, species significantly exceeding the Lewis acidity of SbF5 have been realized and were termed Lewis superacids (LSA). Prospective new candidates emerge steadily, which not only outperform SbF5 by their strength, but also in terms of their accessibility and ease of handling. In principle, Lewis superacids allow us to combine the outstanding activity of Br?nsted superacids with the excellent selectivity of a common Lewis acid. However, the broad application of Lewis superacids in synthesis is all but popular. The present review deals with strong Lewis acids. First, it critically discusses Lewis acidity scaling methods and suggests an extended definition for Lewis superacidity. It then summarizes the properties and applications of the strongest currently known Lewis acids, indexed by the fluoride ion affinity (FIA). The supporting information contains a comprehensive list of experimentally and theoretically derived FIA data as a guide for the choice of Lewis acidic reagents/catalyst. This contribution shall encourage the search for new Lewis superacids and promote their application in non-specialized laboratories.
Gesehen am 15.05.2019